2019
DOI: 10.1139/cjpp-2018-0544
|View full text |Cite
|
Sign up to set email alerts
|

Are the cardioprotective effects of the phytoestrogen resveratrol sex-dependent?

Abstract: Cardiovascular disease (CVD) is the number one cause of death in both men and women. Younger women have a lower risk for CVD, but their risk increases considerably after menopause when estrogen levels decrease. The cardiovascular protective properties of estrogen are mediated through decreasing vascular inflammation and progression of atherosclerosis, decreasing endothelial cell damage by preventing apoptosis and anti-hypertrophic mechanisms. Estrogen also regulates glucose and lipid levels, which are 2 import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 143 publications
0
16
0
Order By: Relevance
“…CVD risk increases with increasing age, gradually in men while disproportionately in women, and such a lower risk was in association with estrogen's cardioprotective properties [107,108]. In a recent in vivo study, sex differences were observed in rats with surgically-induced myocardial infarction (MI) due to the resveratrol treatment (2.5 mg/kg/d) [109]. Superior improvements were observed in females in terms of interventricular septal wall dimension at systole (IVSDs), end-systolic volume (ESV), ejection fraction (EF), fractional shortening (FS), and isovolumic relaxation time (IVRT), among which IVRT was purely sex-dependent.…”
Section: Sex-dependent Effects Of Resveratrolmentioning
confidence: 99%
“…CVD risk increases with increasing age, gradually in men while disproportionately in women, and such a lower risk was in association with estrogen's cardioprotective properties [107,108]. In a recent in vivo study, sex differences were observed in rats with surgically-induced myocardial infarction (MI) due to the resveratrol treatment (2.5 mg/kg/d) [109]. Superior improvements were observed in females in terms of interventricular septal wall dimension at systole (IVSDs), end-systolic volume (ESV), ejection fraction (EF), fractional shortening (FS), and isovolumic relaxation time (IVRT), among which IVRT was purely sex-dependent.…”
Section: Sex-dependent Effects Of Resveratrolmentioning
confidence: 99%
“…It is hypothesized that regular consumption of isoflavone-rich foods provides substrates for equol producing bacteria to thrive, if present [ 123 ]. There are many suggested health benefits of phytoestrogens, including reduced menopausal symptoms, reduced risk of cardiovascular disease, obesity, metabolic syndrome, type 2 diabetes, cognitive disorders, and various forms of cancer [ 124 , 125 , 126 , 127 , 128 ]. Nonetheless, concerns are frequently raised that soy isoflavones and other phytoestrogens may act as endocrine disruptors and stimulate the growth of estrogen-sensitive cancers [ 129 , 130 , 131 , 132 ].…”
Section: Phytoestrogensmentioning
confidence: 99%
“…The cardioprotective activity [ 19 ] and estrogen-dependent cancer protection role of estrogens [ 20 , 21 ] are well-documented. Numerous studies have described the same estrogenic role of resveratrol in these disorders [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Resveratrol Effects On Femalesmentioning
confidence: 99%